Myopathy associated with homozygous PYROXD1 pathogenic variants detected by genome sequencing. Issue 3 (9th February 2020) - Woods, Jeremy D.; Khanlou, Negar; Lee, Hane; Signer, Rebecca; Shieh, Perry; Chen, Johnathan; Herzog, Matthew; Palmer, Christina; Martinez‐Agosto, Julian; Nelson, Stanley F.
Abstract : Biallelic pathogenic variants in the gene PYROXD1 have recently been described to cause early‐onset autosomal recessive myopathy. Myopathy associated with PYROXD1 pathogenic variants is rare and reported in only 17 individuals. Known pathogenic variants in PYROXD1 include missense, insertion and essential splice‐site variants. Here we describe a consanguineous family of individuals affected with late‐onset myopathy and homozygous PYROXD1 missense variants (NM_024854.5:c.464A>G [p.Asn155Ser]) expanding our understanding of the possible disease phenotypes of PYROXD1 ‐associated myopathy.